Influence and Preservation : Utilisation of Human Resources protecting Tangible Cultural Heritage, supported by the Ministry of Culture in Greece - Evangelou, Paraskevi A.; Broni, Georgia K. (Dia-noesis: A Journal of Philosophy, 2025)
Cultural Heritage defines a country. The preservation of Cultural Heritage is linked to the principles it has as a country and as a society. Citizens, based on these values, feel safe and stable. Tangible cultural assets are physical objects or structures that have artistic, historical or cultural significance. In Greece, according to the law, the protection and preservation of Cultural Heritage is assigned to the Ministry of Culture. The responsibility for achieving this goal lies entirely with the Ministry. By extension, the burden of this responsibility falls on the employees of the Ministry and its services throughout the territory. This study investigates the influence and protection of Tangible Cultural Heritage through the utilisation of Human Resources. The qualitative research tools of questionnaires are combined in the research, so as to explore the contribution of Human Resources to the protection of culture. The research sample consisted of employees of the Ministry of Culture in Greece who work to preserve the Cultural Heritage. The study utilised 603 anonymous Greek respondents. It also involved a survey that took place online using Google Forms. SPSS software was used to process and analyse the primary data. These findings provide valuable insights for the Ministry of Culture and its directors to better support and sustain Tangible Cultural Heritage by leveraging Human Resources, to develop partnerships with institutions and citizens using innovations, while also further expanding the understanding of the need to utilize staff and external factors, as on this issue limited research has been conducted.